STRATEGI PENGEMBANGANGAN PUKAT CINCIN (PURSE SEINE) DI NEGERI WAAI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Joel Kaihena; Welem Waileruny; Selfi Sangadji (Universitas Pattimura, 2024)
The operation of purse seine fishing gear already exists and is utilized by fishermen in Waai Country, which is administratively located in Salahutu sub-district, Central Maluku Regency. The objectives of this research are: 1) Analyze the socio-economic aspects of purse seines in Waai Country; 2) Describe the purse seine fishing unit; 3) Formulate a strategy for developing the purse seine business in Waai Country. The people of Waai State, whose main profession is purse seine fishermen, also have other jobs, including as motorbike taxi drivers and farmers, to support their family's economic needs and their education is much better, the results of research show that to determine which strategy is best. will be used in the development of purse seine fishing in Negeri Waai, Salahutu District, Central Maluku Regency, so the analysis data obtained is that the results of the analysis are in quadrant 1, so the strategy used is the SO strategy including: 1) Increase production, 2) Use efficient technology, 3) Facilitate fishermen to get fuel with fisherman card subsidies.